2007
DOI: 10.1002/pssa.200622395
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of CuFeInSe3 from X‐ray powder diffraction data

Abstract: The crystal structure of the adamantane compound CuFeInSe3, belonging to the system (CuInSe2)1–x (FeSe)x with x = 0.5, was analyzed using X‐ray powder diffraction data. Several model structures were derived from the structure of the selenium rich phase CuInSe2.3 by permuting the cations in the available Wyckoff positions. The refinement of the best model by the Rietveld method in the tetragonal space group P$ \bar 4 $2c (Nº 112), Z = 1, with unit cell parameters a = 5.7762(2) Å, c = 11.5982(7) Å and V = 386.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…2 where a comparison is made between the chalcopyrite Cu-IIISe 2 I42d structure and the P42c structure of Cu-Mn-III-Se 3 (III= Al, Ga, In). Therefore, in the quaternary structures, the introduction of an additional cation (Mn) produces an effect of "dilution" of this cation in the chalcopyrite structure leaving the cell volume almost unchanged 6 . Table 5 show a comparison between the unit cell parameters and the bond distances for the three phases of both families of compounds.…”
Section: 4(2) X2mentioning
confidence: 99%
See 1 more Smart Citation
“…2 where a comparison is made between the chalcopyrite Cu-IIISe 2 I42d structure and the P42c structure of Cu-Mn-III-Se 3 (III= Al, Ga, In). Therefore, in the quaternary structures, the introduction of an additional cation (Mn) produces an effect of "dilution" of this cation in the chalcopyrite structure leaving the cell volume almost unchanged 6 . Table 5 show a comparison between the unit cell parameters and the bond distances for the three phases of both families of compounds.…”
Section: 4(2) X2mentioning
confidence: 99%
“…These materials crystallize with tetragonal symmetry in the space group I4 2d (N°122), and the addition of a Fe-Se binary compound produces alloys of the type (Cu-IIISe 2 ) 1-x (FeSe) x 2 . Some previous results on the formation, structural characterization, thermal and magnetic properties on these alloys with compositions Cu-Fe-III-Se 3 (x = ½), Cu-Fe 2 -III-Se 4 (x = ⅔) and Cu 2 -Fe-III-Se 5 (x = ⅓) have been reported [3][4][5][6][7][8][9][10][11][12][13][14][15] . All these phases fulfill the rules of formation of adamantane compounds 2 and belong to the normal semiconductor compound families of the third, fourth and fifth-order derivatives of the II-VI binary semiconductors, respectively 16 .…”
Section: Introductionmentioning
confidence: 96%
“…All the possible phases fulfill the rules for the formation of adamantane compounds (Parthé 1995) giving materials with semiconductor behaviour, which belong to the compound families derivatives of the II-VI binary (Delgado 1998). Recently, it has been shown that when x = 1/2, the formation of alloys with composition I-II-III-VI 3 are obtained (Grima-Gallardo and Ruiz 1999;Grima-Gallardo et al 2001a, b;Mora et al 2007). In a recent work carried out on the CuFeInSe 3 material (Mora et al 2007), it was found that this compound crystallizes in a primitive tetragonal structure with space group P4 -2c.…”
Section: Introductionmentioning
confidence: 95%
“…Structural studies carried out on some members of this family indicate that they crystallize in a sphalerite derivative structure (stannite) with tetragonal space group I 4 2m (No. 121) 11 , or in a wurtzite derivative structure (wurtzite- In recent years, it has been of interest to carry out a systematic study of the crystal structure of quaternary diamond-like families [13][14][15][16][23][24][25][26] . Hence, in this work we report the X-ray powder diffraction analysis and crystal structure of the quaternary compounds CuCo 2 InTe 4 and CuNi 2 InTe 4 , two new members of the I-II 2 -III-VI 4 family, which crystallize with a stannite structure.…”
Section: Introductionmentioning
confidence: 99%